CURRICULUM IMPLEMENTATION 2013 IN LEARNING NEGOTIATED TEXT IN CLASS V MI NURUL KARIM NW KEBON AYU - Ahmad Fathoni; Zainul Arifin; Supriyanto (Al-mujahidah, 2023)
This study aims to describe (1) negotiation text lesson planning based on 2013 curriculum in Class V MI Nurul Karim NW Kebon Ayu, (2) implementation of negotiation text lesson based on 2013 curriculum in Class V MI Nurul Karim NW Kebon Ayu and (3) obstacles experienced by teacher in text learning negotiation based on curriculum 2013 in Class V MI Nurul Karim NW Kebon Ayu. The design of the research used is the descriptive research design. The subjects of this study are students and teachers in Grade V MI Nurul Karim NW Kebon Ayu academic year 2017/2018. Data collection in this research using observation method, interview, and documentation. Data obtained through the three methods are processed through several stages, namely (1) data reduction, (2) data classification, (3) data presentation, and (4) conclusion. The result of research generally proves that learning of text of nogosiasi based on curriculum 2013 in Grade V of MI Nurul Karim NW Kebon Ayu student has been successful. This is evident from the results achieved by students in text lessons nogosiasi based on the 2013 curriculum that has reached the value above the KKM. In learning nogosit text based on the 2013 curriculum, teachers use several methods, namely lecture method, discussion, question and answer, and assignment. The obstacles that teachers face when teaching text nogogues based on the 2013 curriculum are seen in the selection of suitable models. The lack of understanding of teachers in determining the model of learning in accordance with the material and condition of students. Based on these findings it can be concluded that the planning and implementation of learning used by teachers is in accordance with the curriculum of 2013 but there are still shortcomings, ie setting the time or lesson less appropriate RPP, media not used in the learning process, and teacher constraints lies in the lack of understanding of teachers to use learning model.